TRATAMENTO FUNGICIDA DE SEMENTES DE SOJA NO TESTE DE ENVELHECIMENTO RÃPIDO - Marcos Filho, Julio; Shioga, Pedro S. (REVISTA DE AGRICULTURA, 2015)
TRATAMENTO FUNGICIDA DE SEMENTES DE SOJA NO TESTE DE ENVELHECIMENTO RÃPIDO